Elaboração e avaliação de hambúrgueres de carne bovina com substituições de toucinho por farinha de linhaça - Silva, Carlos Eduardo da (2013)
Hamburger is a food very appreciated by people of different ages. Children and adolescents are the main consumers, but adults also have consumed habits this type of the foods. Aiming to improve the nutritional quality of the product, this study added flaxseed meal in beef hamburgers as replacing pork fat. The objective was to develop and evaluate the physical, physicochemical, major minerals and lipid profile of burgers cattle added flaxseed meal replacing pork fat in the form fresh, grilled and fried. The results of the cooking characteristics showed that the burgers with the highest percentage of linseed meal had higher moisture retention capacity and thus higher yield in both forms of heat treatment (frying and grilling) contributing to softness and juiciness. The results of physicochemical analyzes showed an increase in carbohydrate content due to the addition of linseed meal. The analysis of fatty acids of the total lipids of burgers resulted in an increase of the content of linolenic acid (18:3 n-3). Both for grilled burgers and fried for the content of linolenic acid increased from approximately 0.7% (F1 - 0% flaxseed meal) to 21% (F5 - 10% flaxseed meal), which contributed to reducing the ratio of omega-6 (n-6) to omega-3 (n-3), making the burgers supplemented with flaxseed meal one most suitable food in nutritional terms. The content of the minerals iron, potassium, magnesium, sodium and zinc, decreased as the substitution of fat by increasing linseed meal, with the exception of phosphorus that increased by about 10 times for burgers with pork fat totally replaced by linseed meal. The amount of malondialdehyde was greater for fried burgers than for grilling and even lower for raw burgers, and the ones with higher amounts of linseed meal oxidized the most. The addition of linseed meal burgers as substituents in saturated fat (pork) can be considered a way to improve the nutritional potential, and contribute to better health of the consumer.